Ectopic Splicing Disturbs the Function of Xist RNA to Establish the Stable Heterochromatin State - Matsuura, Ruka; Nakajima, Tatsuro; Ichihara, Saya; Sado, Takashi (Frontiers in Cell and Developmental Biology, 2021)
Noncoding Xist RNA plays an essential role in X chromosome inactivation (XCI) in female mammals. It coats the X chromosome in cis and mediates the recruitment of many proteins involved in gene silencing and heterochromatinization. Molecular basis of how Xist RNA initiates chromosomal silencing and what proteins participate in this process have been extensively studied and elucidated. Its involvement in the establishment and maintenance of the X-inactivated state is, however, less understood. The XistIVS allele we previously reported is peculiar in that it can initiate XCI but fails to establish the inactive state that is stably maintained, and therefore, may provide an opportunity to explore how Xist RNA contributes to establish robust heterochromatin state. Here we demonstrate that ectopic splicing taking place to produce XistIVS RNA disturbs its function to properly establish stable XCI state. This finding warrants the potential of XistIVS RNA to provide further insight into our understanding of how Xist RNA contributes to establish sustainable heterochromatin.